Against Free Speech - Leaker, Anthony (Polemics., 2020)
Leaker critiques the role that the defence of free speech has played in legitimising the scapegoating of oppressed minorities while deflecting attention from the egregious operations of power that have led to ever greater inequality, injustice and capitalist destruction.